Outcomes of palliative‐intent surgery in retroperitoneal sarcoma—Results from the US Sarcoma Collaborative. Issue 7 (13th March 2020) - Thalji, Sam Z.; Tsai, Susan; Gamblin, T. Clark; Clarke, Callisia; Christians, Kathleen; Charlson, John; Ethun, Cecilia G.; Poultsides, George; Grignol, Valerie P.; Roggin, Kevin K.; Votanopoulos, Konstantinos; Fields, Ryan C.; et al.
Abstract: Background and Objectives: Outcomes of palliative‐intent surgery in retroperitoneal sarcomas (RPS) are not well understood. This study aims to define indications for and outcomes after palliative‐intent RPS resection. Methods: Using a retrospective 8‐institution database, patients undergoing resection of primary/recurrent RPS with palliative intent were identified. Logistic regression and Cox‐proportional hazards models were constructed to analyze factors associated with postoperative complications and overall survival (OS). Results: Of 3088 patients, 70 underwent 87 palliative‐intent procedures. Most common indications were pain (26%) and bowel obstruction (21%). Dedifferentiated liposarcoma (n = 17, 24%), leiomyosarcoma (n = 13, 19%) were predominant subtypes. Median OS was 10.69 months (IQR, 3.91‐23.23). R2 resection (OR, 8.60; CI, 1.42‐52.15; P  = .019), larger tumors (OR, 10.87; CI, 1.44‐82.11; P  = .021) and low preoperative albumin (OR, 0.14; CI, 0.04‐0.57; P  = .006) were associated with postoperative complications. Postoperative complications (HR, 1.95; CI, 1.02‐3.71; P  = .043) and high‐grade histology (HR, 6.56; CI, 1.72‐25.05; P  = .006) rather than resection status were associated with reduced OS. However, in R2‐resected patients, development of postoperative complications significantly reduced survival ( P  = .042). Conclusions: Postoperative complications and high‐grade histology rather than resection status impacts survival in palliative‐intent RPS resections. Given the higher incidence of postoperative complications which may diminish survival, palliative‐intent R2 resection should be offered only after cautious consideration.